CARA PENGUSAHAAN HUTAN NIPAH (Nypa pructicans) DI BATU AMPAR KALIMANTAN BARAT - Sukanda Sukanda (Pusat Penelitian dan Pengembangan Hasil Hutan, 1995)
Nipah (Nypa fructicans) is a species of the Palmae family which grows on swampy areas, coastal mid along bankriver. It is commonly known that the tree is able to produce so called nira (fruits) which can be used for sweety material.The utilization and development of wild nypa forest as sweety material has been done by PT Milatronika Karya Nypah Indonesia in Sponti Jaya nypa forest, Sub District of Batu Ampar, Pontianak. In order to produce some amount of nira from nypa, tending and special care particularly to the fruit stems are required. The nira processed into redish sugar, ant sugar, cristle sugar, acid and fresh drinking water is obtained through cutting of the fruit stem.The red fructosa of nira has a composition as follows : sucrose 83, 67 %, reduction sugar2.72 %, total sugar 90,57 %, carbon 4,57 % and The rest in the form of parfume (nipa specific).the other benefits of nypa forest utilization are to create employment and regional development.